Mobile computing, applications, and services : 9th International Conference, MobiCASE 2018, Osaka, Japan, February 28-March 2, 2018, Proceedings /: 9th International Conference, MobiCASE 2018, Osaka, Japan, February 28-March 2, 2018, Proceedings. (2018) - Unknown
No abstract available